Possible Ways of Integrating Digital Technologies and the Internet into EFL Instruction - Váradi Krisztián; Вараді Крістіян (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. Teaching English as a foreign language (EFL) has undergone various changes in the last decades (smartphones, notebooks, tablet PCs, Web 2.0 technologies, online dictionaries). In the given research, foreign language teaching and learning were studied with the help of three different methods: interviews with secondary school teachers, questionnaires with secondary school pupils in Beregszász, and online questionnaires among institute and university students. We can observe from the research findings that teachers should consider using technology more often in their lessons, so the process of teaching would be more successful. The situation is further complicated by the fact that Transcarpathian secondary schools lack the necessary amount of digital devices, because they do not receive enough financial support from the state.

Резюме. За останні десятиліття вивчення англійської мови пройшло через значні зміни (смартфони, ноутбуки, планшети, Веб 2.0 технології, он-лайн словники). За допомогою трьох дослідницьких методів ми проаналізували можливості вивчення та викладання іноземної мови: інтерв’ю із вчителями закарпатських шкіл, опитування берегівських старшокласників, он-лайн анкетування студентів інституту та університету. Результати дослідження свідчать, що процес викладання був би успішнішим, якби вчителі частіше використовували на уроках сучасні технології. Ситуацію ускладнює те, що державне фінансування закарпатських шкіл недостатнє для закупівлі всього необхідного цифрового обладнання.

Az angol mint idegen nyelv tanítása folyamatos változásokon ment át az utóbbi évtizedekben (okostelefonok, notebookok, táblagépek, Web 2.0 technológiák, online szótárak). Három kutatási módszer segítségével vizsgáltam meg az idegennyelvtanítás és -tanulás jelenségét: középiskolai tanárokkal készített interjúk, kérdőíves felmérés beregszászi középiskolásokkal, valamint online kérdőíves felmérés főiskolai és egyetemi hallgatókkal. A kutatás eredményeit figyelembe véve az oktatási folyamat sikeresebben valósulna meg, ha a tanárok a technológiai eszközöket gyakrabban alkalmaznák. A jelen helyzetet nehezíti, hogy a kárpátaljai középiskolákban hiány van a technológiai eszközökből, mivel nem részesülnek megfelelő anyagi támogatásban az állam részéről.
Можливі способи використання цифрових технологій та Інтернету при вивченні англійської мови
A digitális technológiák és az internet használatának lehetséges módjai az angol nyelv oktatásában
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008907
Keywords: digital technologies; Web 2.0; foreign language teaching